Variants in genes related to inflammation and endothelial function can increase the risk for carotid atherosclerosis in southwestern China - Xie, Yong; Yu, Ming; Qing, Ting; Luo, Hua; Shao, Minjie; Wei, Wei; Yi, Xingyang (Frontiers in Neurology, 2023)
Aim: To investigate the association between variants in genes involved in inflammation and endothelial function and carotid atherosclerosis. Results: Among the 2377 subjects with high risk stroke population, 1028 subjects had carotid atherosclerosis (43.2%), of which 852 (35.8%) cases had carotid plaque, 295 (12.4%) cases had ≥ 15% carotid stenosis, and 445 (18.7%) had mean IMT > 0.9 mm. Multivariate logistic regression revealed that IL1A rs1609682 TT and HABP2 rs7923349 TT were independent associated with the risk for carotid atherosclerosis (OR, 1.45, 95% CI: 1.034-2.032, P = 0.031, and OR, 1.829, 95% CI: 1.228-2.723, P = 0.003) . GMDR analysis found that there was a significant gene-gene interaction among IL1A rs1609682, HABP2 rs7923349 and ITGA2 rs1991013. After adjusting the covariates, the high-risk interactive genotypes among the 3 variants were independently associated with a higher risk for carotid atherosclerosis (OR, 2.08, 95% CI: 1.257-5.98, P < 0.001). Conclusion: Prevalence of carotid atherosclerosis was very high in the high risk stroke population in Sichuan of southwestern China. Specific variants in genes involved in inflammation and endothelial function were associated with the carotid atherosclerosis. The high-risk interactive genotypes among IL1A rs1609682, HABP2 rs7923349 and ITGA2 rs1991013 were independently associated with a higher risk for carotid atherosclerosis. The results are expected to provide new targets for prevention and treatment of carotid atherosclerosis.